The Synergy of the Higher Education World in Improving the Results of Accounting Skills of Students of SMK Tritech Informatika Medan - Harianto, Adi; Duffin; Harianto, Yogi Rahman Feriza Ginting; Deva Djohan; Thamrin; Robin; Lidia Berliana Siboro; Mhd Restu Razaq; Kuandi Chandra; Darwan Tanady (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Vocational education must adapt to the demands of the industrial era by integrating academic mastery with practical competencies aligned with industry standards. This community service initiative involves collaboration between SMK Tritech Informatika Medan and a partner university to improve students’ performance in the Accounting Competency Test (UKK). The program focuses on enhancing students’ understanding of accounting concepts and practical applications through intensive mentoring, simulation-based training, and curriculum alignment. The activities engaged 12 students and several instructors through methods such as workshops, guided practice, discussions, and assessments. University lecturers and students served as academic facilitators, offering innovative and interactive learning approaches. The results, measured through pre-test and post-test instruments, indicate a significant improvement in students’ comprehension, confidence, and readiness for the UKK. Furthermore, the program strengthened teachers’ pedagogical capacity and enriched curriculum design with an industry-based perspective. This collaborative model demonstrates the effectiveness of structured synergy between vocational schools and higher education in shaping job-ready graduates and should be considered for wider application across different vocational fields.